A Personalized Medicine Approach to the Diagnosis and Management of Autism Spectrum Disorder - Frye, Richard E.; Boles, Richard; Rose, Shannon; Rossignol, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This collection of articles provides an overview of the current and future methods for applying a personalized medicine approach to the diagnosis, management, and treatment of autism spectrum disorder.